Magnetic activated carbonaceous materials from sugarcane bagasse: Preparation, characterization, and hexavalent chromium removal - Nogueira, Gabriela A. [UNESP]; Fregolente, Laís G.; Pereira, Lorena S. [UNESP]; Laranja, Márcio J. [UNESP]; Moreira, Altair B. [UNESP]; Ferreira, Odair P.; Bisinoti, Márcia C. [UNESP] (Elsevier, 2024)
The presence of hexavalent chromium (Cr (VI)) in effluents remains a global concern due to its toxic properties. Even though adsorption has been employed for its removal from water, developing sustainable materials with higher adsorption capacities is still pivotal to tackling such contamination. In this study, two magnetic carbons (MC) were produced by hydrothermal carbonization (HTC) of sugarcane bagasse in the presence of iron (III) nitrate at 230 and 270 °C. Both MCs were thermochemically activated at 500 and 700 °C using KOH (1:2; w:w). The materials were characterized in terms of composition, structure, morphology, texture, and surface properties and then evaluated in adsorption studies of Cr (VI). After HTC, some iron phases such as α-Fe2O3, γ-Fe2O3, and Fe3O4 were observed, while thermochemical activation additionally revealed Fe0 and Fe4[Fe(CN)6]3. Activation increased the amount of meso- and macropores, specific surface area, pHzpc, surface hydrophilicity, and carbon and nitrogen contents. The adsorption kinetics study indicated that the pseudo-second-order model describes better the behavior of the materials. The investigation of adsorbent dose showed that doses below 1.00 g L−1 were more efficient in Cr (VI) removal. MC-230 and MC-270 thermochemically activated at 700 °C exhibited the highest Cr (VI) adsorption capacities (10.5 and 15.5 mg g−1, respectively). Therefore, the improved adsorption capacity for Cr (VI) of the materials thermochemically activated at 700 °C was mainly due to their enhanced textural properties.
Keywords: Hexavalent chromium removal; Lignocellulosic biomass; Magnetic activated carbon; Thermochemical activation